The Therapeutic Effects of Sevelamer on Blood Sugar, HbA1c, Lipid Profile, and hs-CRP in Patients with Diabetic Nephropathy - Sosan Mohammadi Kebar; Afshan Shargi; Bahman Bashardoust; Manouchehr Iranparvar; Hossein Fekri; Afshin Habibzadeh (Journal of Nephropathology, 2018)
Background: Diabetic nephropathy (DN) is one of the major complications of diabetes. Hyperglycemia, inflammation and oxidative stress as well as advanced glycation end products (AGEs) are reported as the risk factors for DN. Sevelamer has shown promising results in reducing inflammation and even HbA1c levels in DN. Objectives: We aim to evaluate the therapeutic effects of sevelamer on blood sugar, HbA1c level, lipid profile, and high sensitivity CRP (hs-CRP) in patients with diabetic nephropathy. Patients and Methods: In this clinical trial, 18 patients (13 female with mean age of 61.22±9.32 years) with stages 2-4 of diabetic nephropathy were recruited. Patients were administered with 800 mg of sevelamer twice a day for three months. Blood sugar, HbA1C, hs-CRP, lipid profile and other laboratory findings were measured before and 1, 2 and three months after initiation of the treatment. Results: There was significant decline in HbA1c (p=0.001), postprandial blood sugar (p=0.02) and phosphorus (p<0.001) at the end of the study period. Sevelamer had no effect on fasting blood sugar, lipid profile, blood urea nitrogen, creatinine, Na, K and hs-CRP. Conclusion: Our results indicated that along with its phosphorus reducing effects, sevelamer plays an important role in decreasing postprandial blood sugar and HbA1c level. Sevelamer had no effects on lipid profile and hs-CRP.